Production networks, and digital logistics as a tool for regional development: the wood processing industry in the City of Buri, São Paulo - Sguizzardi Abascal, Eunice Helena (2010)
In Brazil municipalities and regions face nowadays plenty of challenges to achieve a sustainable development founded in logistic and productive relationship networks. These networks and respective operations require knowledge and domain of productive possibilities and business opportunities that can develop themselves in regional and endogenous territorial scales. These challenges derive of the fact that municipalities are part of many government and administrative regions in brazilian states to actuate in solidary and synergic way, potentializing relationships with respective congeners. Networks formation requests a rigorous knowledge of the socioeconomic conditions, the municipalities and the regions characters, and it requests TIC (Communication and Information Technologies) instrumental use, being able to give ways to expand and to know the social actors that are related and their potential partners through digital networks. This type of networks enables a synchronic management of territorial and economic complexities, in real time (just in time). This article analyzes by critical way the causes of socioeconomic depression of Sao Paulo State southwest region, with the objective of identifying the responsible factors of its stagnation. It also analyzes specific characteristics of Buri Municipality that is situated in southwest Sao Paulo State region. Showing business networks formation based on the transformation wood industry. This natural product is available in the region, here we investigate the local development possibilities, productive and logistic networks (Material Networks) and we suggest digital networks use. These actions not just only create regional advantages, but indeed releases Sao Paulo metropolis: either its spaces and its circulation highways, unduly congested due vehicle concentration that is responsible by transport, state and federal logistic.